Analisis Nilai-Nilai Profetik Dalam Pembelajaran Al-Qur’an Hadits Siswa Kelas VIII MTSN 1 Wonosobo - Bagus Adi Saputro; Robingun Suyud El-Syam; Ngatoillah Linnaja (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This article reveals the analysis of prophetic values in the learning of Al-Qur'an Hadith of students in class viii MTSN 1 Wonosobo, using descriptive qualitative research, and analyzed interactively. The results showed that the analysis of prophetic values in the learning of Al-Qur'an Hadith of students in class viii MTSN 1 Wonosobo was carried out by observing and analyzing the object of research directly, especially the behavior of students at school, which was carried out through three ways: understanding (knowledge), habituation, and exemplary. The analysis of the Prophetic Values is evident through four indicators: honesty (shiddiq), intelligence (fathonah), responsibility (amanah) and the courage to express opinions loudly (tabligh). Research implications: the importance of teacher supervision and innovation in learning Al-Qur'an Hadith in correlation with the success of prophetic values analysis can be maximized, interpreted and implemented. This study is expected to contribute to the development of Islamic educational institutions to be in accordance with prophetic values.